PD-L1 expression and correlation with outcome in muscle-invasive and metastatic urothelial carcinoma: review and critical discussion - El Saadany, Tämer; Lorch, Anja; Milowsky, Matthew I.; Vogl, Ursula Maria; Cathomas, Richard (Frontiers in Oncology, 2024)
Immunotherapy with checkpoint inhibitors including atezolizumab, pembrolizumab and nivolumab has become an essential pillar in the management of muscle invasive and metastatic urothelial carcinoma. The field has evolved quickly in the past few years and several early beliefs have recently been upended. One such belief relates to the predictive value of PD-L1 expression based on immunohistochemistry. Nevertheless, requirements for PD-L1 expression from regulatory bodies still restrict the use of checkpoint inhibitors in urothelial carcinoma. This article provides a critical review of the available data from the registration trials on which the current regulations have been based with the conclusion that a review of the current approval status incorporating PD-1 expression is warranted.